The psychology student$1 (Bs guide to study and employability /s - Davey, Graham (b)
How does a Psychology degree work? Where will it lead me? What skills are employers looking for? Psychology is one of the most popular undergraduate degree subjects in the UK, which is no surprise given the wide range of transferrable skills it offers. But how to translate these skills into job opportunities? And which career paths to explore? If you are considering studying psychology, or you are already a psychology student looking at your next steps, this book is for you. Written by leading academics, this handy guide interweaves both study skills and employability skills, providing advice across all three years of your course and talking you through the different options open to you after graduation. From writing essays to revising for exams, and from careers in and outside of professional psychology to further academic study, this book covers everything a psychology student needs to know even how to make the most of your social life!
Includes references and index.
Keywords: Psychology -- Vocational guidance -- Great Britain; Psychologies -- Orientation professionally